A Bibliometric Retrospective of Thematics, Collaboration, and Impact in the International Journal of Atharva - Duwal , Bal Ram; Acharya, Meemamsa; Poudel, Binaya; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2025)
Background: The International Journal of Atharva is an important platform for interdisciplinary scholarship, especially on issues pertaining to the South Asian context. A much-needed quantitative, systematic investigation into its publication landscape will provide insight into its intellectual structure, collaborative networks, and scholarly impact-areas that have not been previously explored. Objectives: The present study undertakes a comprehensive bibliometric analysis of the International Journal of Atharva to outline the core research themes, analyze the co-authorship networks, and appraise its interdisciplinary character. Methods: Publication metadata were obtained from the database of Lens.org. The data were analyzed with two main tools, VOSviewer for building and visualizing bibliometric networks of keyword co-occurrence and author collaborations, and wordsift.org to create a word cloud identifying predominant terms in article titles. Findings: The analysis highlights a dominant disciplinary focus on Psychology, Business, and Computer Science with a strong applied research orientation to educational, service-industry, and health-related studies in Nepal. The co-authorship network is decentralized and contains distinct collaborative clusters anchored by prolific authors. Subash Adhikari has been identified as a central connecting node. Key themes emerge on student satisfaction, service quality, and mental health-a research ecosystem deeply engaged with the local socio-economic issues. Conclusion: The International Journal of Atharva demonstrates a strong and distinctive interdisciplinary identity, integrating the social sciences with applied business and health studies. This is reflected in its research output, characterized by robust local relevance and an emerging collaborative network. The journal successfully creates a platform for regionally important, problem-centered research. Implementation: The findings carry implications for the journal editors to identify emerging topics for special issues and refine their strategic direction. Researchers might use this map to identify potential collaborators and niche areas for submission, while libraries and policymakers might learn more from the contribution of this journal to regional scholarship.